In vitro and in silico inhibitory activity of angiotensin-converting enzyme 2 (ACE-2) and anti-inflammatory effects of natural componds from Rheum officinale roots - Khanh, Pham Ngoc; Huong, Tran Thu; Ha, Nguyen Xuan; Anh, Hoang Thi Ngoc; Loc, Vu Thanh; Nghi, Do Huu; Thao, Do Thi; Ha, Trinh Thi Thu; Hung, Nguyen Phi; Ha, Vu Thi; Wessjohann, Ludger A.; Cuong, Nguyen Manh (Vietnam Journal of Science and Technology, 2024)
Rhubarb roots (Rheum officinale), a common medicinal plant in folk remedies, and their chemical compositions were investigated for their inhibitory activity of angiotensin-converting enzyme II and anti-inflammatory effects by inhibiting NO production and IL-6 expression. Four natural compounds, including two anthraquinones, chrysophanol (2) and emodin (3), and two stilbenes, rhapontigenin (1) and trans-piceatannol (4), were isolated from the roots of Rhubarb. The results showed that rhapontigenin (1) exhibited an inhibitory effect on the ACE-2 enzyme with an IC50 value of 132 mM. In an in silico study, rhapotigenin (1) had a binding energy value of -9.32 kcal/mol, lower than MLN-4760, on ACE-2. Both rhapontigenin (1) and emodin (3) exhibited inhibitory activity on NO production in primary cultures of macrophages RAW264.7, with IC50 values ranging from 5.65 to 32.3 µg/mL. This is the first study of the anti-ACE-2 and anti-inflammatory activity of Rhubarb root extract and its constituents.